Blockchain Framework-Based on Halal Assurance System for the Beef Supply Chain - Agus Mansur; Ardan Zaki; Fadhil Adita Ramadhan (Journal of Halal Lifestyle and Sustainability, 2025)
This study aims to design a halal supply chain system integrated with blockchain technology to enhance transparency, traceability, and reliability in the halal certification process. The research addresses systemic limitations of Indonesia’s current halal assurance system, which depends heavily on human intervention and lacks integration among stakeholders. Using Oricow Meatshop Yogyakarta as a case study, the study employs an analytical and simulation-based approach, developing analytical designs, flow diagrams, and Data Flow Diagrams (DFD), and modeling the system through Causal Loop Diagrams (CLD) and Stock and Flow Diagrams (SFD) using Powersim software. The findings propose a consortium blockchain framework with a permissioned voting-based consensus mechanism to ensure data integrity and operational efficiency. The system integrates human and hardware oracles to verify halal-related data and record product movement, while smart contracts automate transaction verification based on halal certification standards. Simulation results show that blockchain implementation improves the halal assurance system’s performance, strengthens transparency, and increases consumer demand for halal products. Theoretically, this research contributes to the understanding of blockchain-based halal supply chains by connecting technological innovation with transparency and trust theories, demonstrating how blockchain mechanisms can be tailored to halal certification. Practically, it provides managerial insights for industry stakeholders to adopt blockchain as a digital infrastructure for credible and efficient halal certification management. However, the study’s scope is limited to a specific case and simulation framework, suggesting the need for broader empirical validation in future research.